PENGARUH PEMBERIAN EKSTRAK AKAR PASAK BUMI (EURYCOMA LONGIFORA JACK) TERSTANDAR TERHADAP GAMBARAN HISTOPATOLOGIK TESTIS TIKUS WISTAR - Miyarso, Condro Suro; Widiastuti, Tri Cahyani; Kiromah, Naelaz Zukhruf Wakhidatul (Jurnal Ilmiah Kesehatan Keperawatan, 2017)
The root of pasak bumi (Eurycoma longifolia, Jack) is one of plant from Indonesia known as aphrodisiac. The study about its standardized extract as aphrodisiac was show increasing libido, testosterone level, FSH and LH on male rats. This study was conducted to evaluate testosterone level and histopathological changes of the testes of male rats of standardized extract of pasak bumi root. There are 50 old male rats which ages 3-4 months old divided to five groups. Group I as negative control was administered aquadestilata. Group II as positive control was administered testosterone (Andriol®). Group III, IV and V ware given standardized extract of pasak bumi root at the dose 50, 100 and 200 mg/kg body weight Respectively. The extract was given orally twice a day for six days and forty nine days and then the testes was taken out on 7th and 50th day. The histopathological of the testes was evaluated using quantitative parameter by the presence of testes weight, number and diameter of Leydig cells. Testosterone level was taken on 7th and 50th day used ELISA method. The results were analyzed using parametric test, one way ANOVA (P<0,05), post hoc Dunnet (2-sided) (P < 0,05). The result of this study shows that the standardized extract of pasak bumi root was not effect on histopathological changes of the testes but it could increased the level of testosterone m at the dose 100 and 200 mg/kg body weight. Key word : Eurycoma longifolia, Jack, aphrodisiac, histopathological testes testosteron